Intertextuality Of The Story Of Prophet Ayub In The Qur'an And The Bible (Julia Kristeva Semiotic Approach) - Muhammad Irfani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2024)
The stories of the prophets narrated by the Qur'an have mostly been explained in the Bible. each holy book in narrating the story of the prophet has its own purpose in conveying messages to its followers. Therefore, the stories of the prophets are important to be studied more deeply. This paper aims to analyze the differences in the narration of the story of prophet Ayub in the Qur'an and the Bible. This research uses qualitative methodology through the intertextual approach pioneered by Julia Kristeva in finding a comparison of the two scriptural narratives. This study concludes through the story of prophet Job contained in the Qur'an and the Bible that there is a reduction of narrative by the Qur'an which creates elements of haplology in each fragment. The suffering of prophet Job narrated by the Qur'an is the work of the devil. While the narrative told in the Bible is the devil. However, the general difference between the narratives of the two books is in terms of the themes raised. The Qur'an raises the theme of faithfulness and patience of Prophet Job, while the Bible carries the theme of suffering and piety of Prophet Job.